Myeloid-derived PD-L1 characterizes spatially organized immune architecture in colorectal cancer - Wu, Qian; Tissot, Stephanie; Peddle, Allyson; Yin, Ke; Sagaert, Xavier; De Hertogh, Gert; Abdelkader, Benyagoub; Pu, Ting; Van Herpe, Filip; D’Hoore, André; Rusakiewicz, Sylvie; Verbandt, Sara; et al. (Frontiers in Immunology, 2026)
IntroductionThe tumor immune microenvironment (TIME) is highly heterogeneous and strongly influences immunotherapy outcomes and patient prognosis in colorectal cancer (CRC). In this exploratory study, we used three multiplex immunofluorescence (mIF) assays to characterize the spatial immune microenvironment associated with high CD8/PD-L1 infiltration.MethodsThree mIF assays quantified the cell densities (cells/mm2) of CD3, CD8, PD-L1, PD-1, CD163, CD56, CD4, Foxp3, Granzyme B (GrzB), CD20, CD11c, CD15, Ki67, and cytokeratin (CK) in the invasive margin (IM) and tumor center (TC) using digital image analysis. Patients were stratified based on CD8/PD-L1 densities and their proximity (cut-off: 20μm) in IM and TC. Immune microenvironment composition was compared between high and low infiltration groups across IM and TC.ResultsPD-L1 expression was predominantly driven from stromal and immune cells with enrichment at IM versus TC, particularly on CD163+ macrophages. Patients with high CD8/PD-L1 infiltration demonstrated significantly increased densities of CD20+, CD3+, PD-1+, CD8+PD-1+, and CD56+ natural killer (NK) cells across tumor tissue, specifically enriched at IM. CD4+Foxp3+ regulatory cells positively correlate with PD-1+, CD8+PD-1+, and CD56+ cells in IM but not TC.ConclusionsThis exploratory mIF analysis identifies PD-L1 expression predominantly on stromal and immune cells, enriched in IM, particularly on CD163+ macrophages. High CD8/PD-L1 tumors display spatially organized IM-specific immune niches featuring coordinated effector-regulatory interactions. Comprehensive spatial profiling of IM-enriched populations, including B cells, CD163+ macrophages, regulatory T cells, and NK cells alongside CD8/PD-L1, may refine patient stratification for immunotherapy in CRC.